Corporate social responsibility in Asia - Fukukawa, Kyoko (Routledge international business in Asia series, 2010)
Examines the theory and practice of Corporate Social Responsibility (CSR) in countries across Asia, including China, Japan, Malaysia, Thailand and Bangladesh, providing Asian perspectives on this important issue. Arguing that Western CSR has enjoyed limited effectiveness, this book asks whether Asia can avoid the West's mistakes.